2023
DOI: 10.1186/s40545-023-00573-w
|View full text |Cite|
|
Sign up to set email alerts
|

Obtaining medication histories via telepharmacy: an observational study

Abstract: Background Medication reconciliation is an effective strategy to reduce medication errors upon hospital admission. The process involves obtaining a best possible medication history (BPMH), which can be both time-consuming and resource-intensive. During the COVID-19 pandemic, telepharmacy was used to reduce the risk of viral transmission. Telepharmacy is the remote provision of pharmacy-led clinical services, such as obtaining BPMHs, using telecommunications. However, the accuracy of telephone-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], it was reported that there was an error in the Funding declaration. The correct Funding declaration is:…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that there was an error in the Funding declaration. The correct Funding declaration is:…”
mentioning
confidence: 99%